Acute Dosing and p53-Deficiency Promote Cellular Sensitivity to DNA Methylating Agents - Gareth Jenkins (Toxicological Sciences, 2015)
Risk assessment of human exposure to chemicals is crucial for understanding whether such agents can cause cancer. The current emphasis on avoidance of animal testing has placed greater importance on in vitro tests for the identification of genotoxicants. Selection of an appropriate in vitro dosing regime is imperative in determining the genotoxic effects of test chemicals. Here, the issue of dosing approaches was addressed by comparing acute and chronic dosing, uniquely using low-dose experiments. Acute 24h exposures were compared with equivalent dosing every 24h over 5-day, fractionated treatment periods. The In Vitro Micronucleus Assay was used to measure clastogenicity induced by methyl methanesulphonate (MMS) and N-methyl-N-nitrosourea (MNU) in human lymphoblastoid cell line, TK6. Quantitative RT-PCR was used to measure mRNA level induction of DNA repair enzymes. Lowest observed genotoxic effect levels (LOGELs) for MMS were obtained at 0.7μg/ml for the acute study and 1.0μg/ml for the chronic study. For acute MNU dosing, a LOGEL was observed at 0.46μg/ml, yet genotoxicity was completely removed following the chronic study. Interestingly, acute MNU dosing demonstrated a statistically significant decrease at 0.009μg/ml. Levels of selected DNA repair enzymes did not change significantly following doses tested. However, p53-deficiency (using the TK6-isogenic cell line, NH32) increased sensitivity to MMS during chronic dosing, causing this LOGEL to equate to the acute treatment LOGEL. In the context of the present data for two alkylating agents, chronic dosing could be a valuable in vitro supplement to acute dosing and could contribute to reduction of unnecessary in vivo follow-up tests